Conformational Change Induced by Putidaredoxin Binding to Ferrous CO-ligated Cytochrome P450cam Characterized by 2D IR Spectroscopy - Ramos, Sashary; Basom, Edward J.; Thielges, Megan C. (Frontiers in Molecular Biosciences, 2018)
The importance of conformational dynamics to protein function is now well appreciated. A current question is how they are involved in the effector role played by putidaredoxin (Pdx) in its reduction of the O2 complex of cytochrome P450cam (P450cam), an archetypical member of the cytochrome P450 superfamily. Recent studies have reported that binding of Pdx induces a conformational change from a closed to an open state of ferric P450cam. A similar conformational change does not appear to occur for the ferrous, CO-ligated enzyme; however, previous studies have noted spectral perturbation upon Pdx binding. To better understand how Pdx binding impacts ferrous, CO-ligated P450cam, we applied 2D IR spectroscopy to compare the conformations and dynamics of wild-type (wt) enzyme in the absence and presence of Pdx, as well as of L358P P450cam (L358P), which has served as a putative model for the Pdx complex. The CO vibrations of the Pdx complex and L358P report population of two conformational states in which the CO experiences distinct environments. The dynamics among the CO frequencies indicate that the energy landscape of substates within one conformation are reflective of the closed state of P450cam, and for the other conformation, differ from the free wt enzyme, but are equivalent between the Pdx complex and L358P. The two states co-populated by the Pdx complex are postulated to reflect a loosely bound encounter complex and a more tightly bound state, as is commonly observed for the dynamic complexes of electron transfer proteins. Significantly, this study supports that the binding of Pdx to ferrous, CO-ligated P450cam does perturb the conformational ensemble in a way that might underlie the effector role of Pdx.